LEGAL ASPECT OF CONSULTATION WITH DOCTOR VIA ONLINE SYSTEM IN INDONESIA - Karo Karo, Rizky; Pasaribu, Debora (Universitas Tadulako, 2018)
Development of technology, communications and the internet make people life easier and faster. Online systems provide changes to buy foods & goods, reserve online transportation even to get consultation with doctor. This research aims to examine the legal aspects of online consultation between doctor and patient or users, about the limitations that can be given in the consultation. The method used is the normative juridical method, using secondary data in the form of books, journals, articles and related regulations and data analysis techniques used are qualitative descriptive. The results of the study: (1). People can consult & communicate with doctors through the online medium by providing true information about their disease history, use of certain drugs and doctors would give the opinions according to the patient's information and the code of ethics; (2). The consultation of doctors through online media obeyed to the Law on Technology & Information, the Health Act, the Medical Practice Act, Consumer Protection Act.Key words: doctor, online consultation, patient, law on techology and informationKey words: doctor, online consultation, patient, law on techology and information